Multiple Layers of Posttranslational Regulation Refine Circadian Clock Activity in Arabidopsis - Seo, Pil Joon (American Society of Plant Biologists, 2014)
The circadian clock is a cellular time-keeper mechanism that regulates biological rhythms with a period of ∼24 h. The circadian rhythms in metabolism, physiology, and development are synchronized by environmental cues such as light and temperature. In plants, proper matching of the internal circadian time with the external environment confers fitness advantages on plant survival and propagation. Accordingly, plants have evolved elaborated regulatory mechanisms that precisely control the circadian oscillations. Transcriptional feedback regulation of several clock components has been well characterized over the past years. However, the importance of additional regulatory mechanisms such as chromatin remodeling, protein complexes, protein phosphorylation, and stability is only starting to emerge. The multiple layers of circadian regulation enable plants to properly synchronize with the environmental cycles and to fine-tune the circadian oscillations. This review focuses on the diverse posttranslational events that regulate circadian clock function. We discuss the mechanistic insights explaining how plants articulate a high degree of complexity in their regulatory networks to maintain circadian homeostasis and to generate highly precise waveforms of circadian expression and activity.